Nurses’ behaviour in the treatment of wounds in an intensive care unit - Moreira, Rosa Aparecida Nogueira; Queiroz, Terezinha Almeida; Araújo, Márcio Flávio Moura de; Araújo, Thiago Moura de; Caetano, Joselany Áfio (Rev Rene, 2009)
This is an exploratory study whose data were collected during the months of January and February 2007 in an intensive care unit in Fortaleza-CE. The aim of the study was to check the behavior of nurses in a public hospital in Fortaleza-CE on the treatment of wounds. The data collection was given through the record of a structured form. All the nurses said to accomplish the record of care and adopt some criteria of evaluation, specific to wounds. Regarding the assessment criteria emphasized: the presence of exudate (56.2%), the extent, depth and type of tissue, all of which with 43.7% of the answers. About 93.7% of the subjects surveyed consider the work important in the multidisciplinary treatment of wounds. It was found that nurses are well aware of the therapeutic methods in the treatment of wounds.